A nitrogen-doped carbon skeleton derived from biomass as conductive agent for electrochemically stable cathode of all-solid-state lithium-sulfur batteries. (March 2023) - Jin, S.; Wang, M.; Zhong, Y.; Wang, X.; Gu, C.; Xia, X.; Tu, J.
Abstract: All-solid-state lithium–sulfur batteries (ASSLSBs) have attracted much attention for the next-generation storage system due to their high energy density and safety. However, the oxidative and reductive decomposition of sulfide electrolyte during cycling causes limited application of ASSLSBs. Herein, we design a porous nitrogen-doped carbon skeleton derived from biomass material. The porous design minimizes the adverse effect of volume change of sulfur. Meanwhile, the introduction of N-doped carbon skeleton improves the electronic conductivity of composite cathode and the sulfur on this skeleton reduces direct contact between the electronic conductor and sulfide electrolyte, thus effectively promoting rapid electron transfer and inhibiting electron aggregation on the surface of electrolyte. Therefore, such an efficient electron transfer network notably suppresses the irreversible decomposition of electrolyte and enhances its cycling stability during charge/discharge process. The composite cathode delivers initial discharge capacity of 1145.9 mAh/g and a capacity retention of 88.14% after 100 cycles at 0.1 C. Highlights: An efficient electron transfer skeleton is fabricated from biomass material. S–C composite cathode stability against decomposition of Li6 PS5 Cl is enhanced. High specific capacity and remarkable cyclic stability of all-solid-state lithium–sulfur batteries are achieved.